Pengaruh Due Professional Care, Akuntabilitas, Integritas terhadap Kualitas Audit (Studi Empiris pada Kantor Akuntan Publik di Surabaya) - Siti Khusnul Khotimah; Syaiful (Jurnal Inovasi Bisnis Manajemen dan Akuntansi, 2024)
This study aims to examine the influence of Due Professional Care, Accountability, Integrity on Audit Quality at Public Accounting Firms in Surabaya. This type of research is quantitative research. The population of this research is all auditors who work at the Public Accounting Firm (KAP) in the city of Surabaya. The sampling method in this research is the purposive sampling method, namely selecting samples based on predetermined criteria and obtaining 56 auditors as respondents. The data used in this research is primary data using a distributed questionnaire. The analytical method used is multiple linear regression analysis using the IMB SPSS Statistics 22 program. The results of this research show that the variables due professional care, accountability, integrity influence audit quality